Enterprise risk management (ERM) and firm value: The mediating role of investment decisions - Faisal Faisal; Zainal Abidin; Haryanto Haryanto (Cogent Economics & Finance, 2021)
The purpose of this study is to examine the mediating effect of investment decisions on the relationship between Enterprise Risk Management (ERM) and firm value. Two hundred and twenty-four companies listed on the Indonesia Stock Exchange for period 2017-2018 were selected as sample by applying Slovin's formula. We used path analysis and Sobel test to check the mediating effect of investment decisions. Our results show that the implementation of ERM in Indonesia public listed companies is still in the initial stage. In addition, the regression tests show that ERM and investment decisions have a positive effect on firm value. The path analysis and Sobel's test results show that investment decisions act as partial mediation on the relationship between ERM and firm value. The study suggests that ERM contributes in improving the effectiveness of investment decisions and firm performance. Therefore, the significant role of stakeholders in increasing the maturity level of ERM is very essential, especially in Indonesia, where the level of risk maturity is still at the initial level. Studies that test the influence of risk management maturity on firm value are still rare, especially in developing country. While, Farrell and Gallagher (2019) have tested the relationship between ERM maturity and firm value, nevertheless they have not considered the role of investment decision in the intermediating the relationship between ERM maturity and firm value.
Keywords: 330; Enterprise risk management; ERM; firm value; Indonesia; investment decisions; resource-based theory